2021
DOI: 10.3138/cpp.2020-119
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Family Stress and Domestic Violence: Lessons from the COVID-19 Outbreak

Abstract: We study Canadians’ concerns regarding the impact of COVID-19 on domestic violence and family stress. Our empirical analysis relies on a unique survey conducted online, the Canadian Perspective Survey Series, which allows us to investigate the determinants of concerns of family stress and domestic violence during the first COVID-19 lockdown. We find no evidence that changes in work arrangements are related to concerns of family stress and violence in the home. In contrast, we find that the inability to meet fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Previous studies showed that parents with children at home reported unique pressures, including worrying about their children’s physical and mental health, education, and the stress of looking after their children while continuing to work [ 29 , 31 ]. Actions such as social distancing, sheltering in place, restricted travel, and closures of key community resources are likely to dramatically increase the risk of family violence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that parents with children at home reported unique pressures, including worrying about their children’s physical and mental health, education, and the stress of looking after their children while continuing to work [ 29 , 31 ]. Actions such as social distancing, sheltering in place, restricted travel, and closures of key community resources are likely to dramatically increase the risk of family violence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of forced and constant presence at home impacted the quantity of domestic chores and childcare (Farré et al, 2021;Del Boca et al, 2020), the occurrence of domestic tensions (Biroli et al, 2021), and even intimate partner violence (i.e. Arenas-Arroyo et al, 2021;Beland et al, 2021). Helplines observed a dramatic rise of distress calls in western countries (Leslie & Wilson, 2020;Bullinger et al, 2021;Miller et al, 2020) as well as in developing countries (Agüero, 2021;Perez-Vincent & Carreras, 2020).…”
Section: * * *mentioning
confidence: 99%
“…To our knowledge, there is less evidence of conflicts between partners during the pandemic. Arenas-Arroyo et al (2021), Beland et al (2021), andHsu &Henke (2021) have documented an increase in domestic violence and family tensions during the lockdown. Berniell & Facchini (2021) document an increase in Google searches of topics related to domestic violence in European and Latin American countries, a few weeks after the beginning of the lockdown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The support from home visitors is especially needed during periods of adversity, such as the ongoing COVID‐19 pandemic, when uncertainty and disruption in daily lives can result in elevated levels of stress and hardship upon families (Seddighi et al., 2021 ; Williams et al., 2021 ). Studies conducted during the pandemic already indicated increases in family stress, caregiver mental health disorders, and domestic violence (Béland et al., 2021 ; Boserup et al., 2020 ; Cluver et al., 2020 ; Puertas‐Gonzalez et al., 2021 ), making the continuity of home‐visiting services during emergencies paramount to child and caregiver health and well‐being.…”
Section: Introductionmentioning
confidence: 99%